TRANSFORMASI KESADARAN SOSIAL ANAK MELALUI PROSES BELAJAR MENGAJAR - Hasanah (Al'Adalah, 2016)
Students, was not only prepared to be himself, but becomes itself in the social environment. In the process of teaching and learning, shaping the child's personality to be good not only educate merely intellectual, but no less important is emotional intelligence (EQ). With emotional intelligence, students can be sensitive to himself, his fellow man, his environment. Problem fun-damendal this study its related to the social awareness who can go by deve-lopment emotional question intelligence through the learning process. Keywords:,.